Habitat Deterioration of The Golden Horn Bill (Aceros undulatus) in Tahura Pocut Meurah Intan - Kamal, Samsul; Mulyadi, Mulyadi (Biotik, 2025)
Pocut Meurah Intan Forest Park, also referred to as Tahura Pocut Meurah Intan, is a protected region located in Aceh Province. The transformation of forested lands into single-crop plantations is leading to significant alterations in the ecological environment. The practice of wood gathering through logging in various sections of the Tahura Pocut Meurah Intan region is interfering with the natural habitats of numerous animal species. This research aimed to assess the habitat loss of the golden hornbill (Aceros undulatus) within Tahura Pocut Meurah Intan. The approach employed for this investigation was an exploratory survey. Data was gathered through a combination of techniques, including the line transect method, concentration count method, and quadrat method. Findings indicated that the habitat degradation affecting the golden hornbill (Aceros undulatus) in Tahura Pocut Meurah Intan was alarmingly severe. In 2021, the extent of habitat damage in the Tahura Pocut Meurah Intan area rose to 2 hectares of primary forest and 21 hectares of tree canopy loss.